EFEK SUPLEMENTASI LAKTOFERIN PADA SUSU FORMULA TERHADAP AVAILABILITAS ZAT BESI, OKSIDASI LEMAK DAN PERTUMBUHAN Escherichia coli PADA SALURAN PENCERNAAN TIKUS [The Effects of Lactoferrin Supplementation to Infant Formula on Iron Availability, Lipid O - Enny Purwati Nurlaili; Mary Astuti; Y. Marsono (Jurnal Teknologi dan Industri Pangan, 2002)
A research on lactoferrin  supplementation to infant formula has been conducted. The objectives of this research were to study the effects of consumption of the supplemented formula on iron availability, lipid oxidation and  growth of Escherichia coli in the intestine. Fifthly newly born rats and their mother (10 rats) were used.They were divided into  5 groups of 10 newly born and 2 mother rats, and were given five different infant formula respectivelly i.e. FEAN (inorganic Fe supplementation), FEOR ( lactoferrin supplementation), FECAMP (inorganic and lactoferrin supplementation), Control (no  Fe supplementation) and Placebo. FeSO4. 7 H2O and lactoferrin were used as the source of inorganic and organic Fe respectively. During the experiment the rat baby also got regular milk from their mothers which were fed by AIN 93 diet. After 30 days  of intervention, blood were withdrawn from the retro orbital plexus for Hb, Fe and TBARS determination. The rats were executed and liver was taken for Fe and TBARS analysis and large intestine were withdrawn for Escherichia coli determination. It was found that Fe supplementation of the formula have no effects on the serum total Fe, increase the total hemoglobin of the baby but was not significantly different between the sources of the Fe. Total Fe of the liver was highest in FECAMP and FEOR rats (101.3 ppm and 83.38 ppm, respectively) and lowest in the Placebo groups (58.1 ppm). Inorganic Fe supplementation increase TBARS of the serum and liver of the rats. Number of total Escherichia coli was lowest in FEOR groups (1.7 10 7 cfu ) and was highest in FEAN rats (7.5 10 7   cfu).